Developmental contexts and features of elite academy football players: Coach and player perspectives - Morley, D.; Morgan, G.; McKenna, J.; Nicholls, A. R. (International Journal of Sports Science and Coaching, 2014)
Player profiling can reap many benefits; through reflective coach-athlete dialogue that produces a profile the athlete has a raised awareness of their own development, while the coach has an opportunity to understand the athlete`s viewpoint. In this study, we explored how coaches and players perceived the development features of an elite academy footballer and the contexts in which these features are revealed, in order to develop a player profile to be used for mentoring players. Using a Delphi polling technique, coaches and players experienced a number of `rounds` of expressing their opinions regarding player development contexts and features, ultimately reduced into a consensus. Players and coaches had differing priorities on the key contexts of player development. These contexts, when they reflect the consensus between players and coaches were heavily dominated by ability within the game and training. Personal, social, school, and lifestyle contexts featured less prominently. Although `discipline` was frequently mentioned as an important player development feature, coaches and players disagreed on the importance of `training`.